2015
DOI: 10.1371/journal.pone.0123915
|View full text |Cite
|
Sign up to set email alerts
|

Health and Economic Impacts of Eight Different Dietary Salt Reduction Interventions

Abstract: BackgroundGiven the high importance of dietary sodium (salt) as a global disease risk factor, our objective was to compare the impact of eight sodium reduction interventions, including feasible and more theoretical ones, to assist prioritisation.MethodsEpidemiological modelling and cost-utility analysis were performed using a Markov macro-simulation model. The setting was New Zealand (NZ) (2.3 million citizens, aged 35+ years) which has detailed individual-level administrative cost data.ResultsOf the most feas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(105 citation statements)
references
References 47 publications
4
99
0
2
Order By: Relevance
“…A total of 1351 articles were identified. After screening and applying the eligibility criteria, fourteen full economic analyses (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) describing cost-effectiveness of salt reduction in Australia, Europe, New Zealand and the USA were included. Figure 1 shows the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1351 articles were identified. After screening and applying the eligibility criteria, fourteen full economic analyses (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) describing cost-effectiveness of salt reduction in Australia, Europe, New Zealand and the USA were included. Figure 1 shows the study selection process.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, studies were heterogeneous in the way interventions and outcomes were modelled and reported, limiting between-study comparisons. As regards the type of nutrient reformulated, 20 studies focused exclusively on sodium reduction (60.6%) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], followed by 5 studies considering at least 2 different nutrients (15.1%) [8,[42][43][44][45], 5 studies addressing sugar (15.1%) [46][47][48][49][50] and 3 study addressing fat (9%) [11,51,52].…”
Section: Resultsmentioning
confidence: 99%
“…This limited between-study comparisons, since results were sensitive to the time horizon of the analysis, the size of the modelled population, and baseline risk factors, which varied across studies. In the studies for which it was possible to calculate gains per 100,000 population, reductions in the sodium content of foods resulted in an increase between 265 QALYs and 12,783 QALYs [28][29][30], or in a reduction between 6.35 and 1452 DALYs [23,24,36]. Although based on less studies, results seem to be consistent across models, showing a positive association between sodium reductions and QALYs (DALYs) gained (lost).…”
Section: Interventions Aiming To Reduce Sodium Intakementioning
confidence: 96%
See 1 more Smart Citation
“…For example, a number of European governments aim to reduce sodium intakes by regulating the maximal level of sodium in bread [7,8]. This action is supported by various modeling studies that suggest both health and economic advantages of reducing sodium in bread (e.g., for Argentina [9][10][11], Australia [12,13], New Zealand [14] and South Africa [15]). Furthermore, there have been successful studies and interventions to replace sodium chloride in bread with potassium salts [16][17][18].…”
Section: Introductionmentioning
confidence: 99%